2022
DOI: 10.24843/lkjiti.2022.v13.i03.p06
|View full text |Cite
|
Sign up to set email alerts
|

HiT-LIDIA: A Framework for Rice Leaf Disease Classification using Ensemble and Hierarchical Transfer Learning

Abstract: Rice is one of the global most critical harvests, and a great many people eat it as a staple eating routine. Different rice plant diseases harm, spread, and drastically reduce crop yields. In extreme situations, they may result in no grain harvest at all, posing a severe threat to food security. In this paper, to amplify the recognition ability for rice leaf disease (RLD) classification, we proposed hierarchical transfer learning (HTL) methods incorporating ensemble models containing two-step. In the first ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…The authors of [32] used the WS-DAN algorithm and reported a testing accuracy of 87.60% for all classes. The authors of [33] used the HTL algorithm and reported a validation accuracy of 91% for three classes: brown spot, hispa, and leaf blast. The authors of [34] used a Lightweight CNN model and reported a testing accuracy of 73.02% for all classes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [32] used the WS-DAN algorithm and reported a testing accuracy of 87.60% for all classes. The authors of [33] used the HTL algorithm and reported a validation accuracy of 91% for three classes: brown spot, hispa, and leaf blast. The authors of [34] used a Lightweight CNN model and reported a testing accuracy of 73.02% for all classes.…”
Section: Resultsmentioning
confidence: 99%
“…They utilized a weakly supervised data augmentation network (WS-DAN) and obtained a testing accuracy of 87.60%. Putra et al [33] proposed a novel methodology known as Hierarchical Transfer Learning (HTL), wherein they utilized pretrained models such as DenseNet, XceptionNet, and MobileNet for feature extraction. Subsequently, the models were assembled and fused.…”
Section: Related Workmentioning
confidence: 99%
“…Jamur, bakteri, virus dan hama adalah organisme yang dapat mengakibatkan penyakit pada tanaman padi [5]. Penyakit dan hama pada tanaman padi dapat mengganggu pertumbuhan tanaman padi, karna penyakit dan hama tersebut dapat mengganggu proses fotosintesis pada tanaman dan menimbulkan perubahan pada bentuk dan warna [6] pada tanaman padi yang diserang. Secara tradisional deteksi penyakit padi dilakukan dengan memberikan sampel tanaman yang terkena penyakit kepada tenaga ahli, dari sampel tersebut tenaga ahli akan mengidentifikasi penyakit tersebut, hal ini tentu akan memakan banyak waktu jika terimplementasikan pada pertanian besar [7].…”
unclassified